2014
DOI: 10.5604/15093492.1135120
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Craniosacral Therapy in Treatment of Patients with Non-specific Low Back Pain. Preliminary Report.

Abstract: STRESZCZENIEWstęp. Nie spe cy ficz ne ze spo ły bó lo we dol ne go od cin ka krę go słu pa to co raz częst sza do le gli wość na rzą du ru chu czło wie ka. Ce lem pra cy by ło zba da nie przy dat no ści tech nik te ra pii czasz ko wo -krzy żo wej w le cze niu do le gli wo ści prze cią że nio wych krę gosłu pa lę dźwio wo -krzy żo we go i po rów na nie jej sku tecz no ści z uzna ną te ra pią punk tów spu sto wych.Ma te riał i me to dy. W ba da niu udział wzię ło wy bra nych lo so wo 55 osób (w wie ku 24-47 lat)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Among the included studies 2 were found to have a high risk of bias [35,46]; for 9 there was major doubt regarding the risk of bias [33,34,3641,43] and 3 were evaluated as having a low risk of bias [42,44,45] (Figs 5 and 6). The principle sources of bias found in studies were the absence of a principal evaluation criterion, lack of correction method for inflated alpha values, no interpretation of the clinical relevance of the results, lack of comparability between proposed treatments and subjective evaluation with an unclear or non-existent blinding method…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies 2 were found to have a high risk of bias [35,46]; for 9 there was major doubt regarding the risk of bias [33,34,3641,43] and 3 were evaluated as having a low risk of bias [42,44,45] (Figs 5 and 6). The principle sources of bias found in studies were the absence of a principal evaluation criterion, lack of correction method for inflated alpha values, no interpretation of the clinical relevance of the results, lack of comparability between proposed treatments and subjective evaluation with an unclear or non-existent blinding method…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the efficacy of techniques used in cranial osteopathy, our review shows that for 14 studies meeting our inclusion criteria, only three had a low risk of bias [42,44,45], for nine there was major doubt regarding the risk of bias [33,34,3641,43] and two were rated with high risk of bias [35,46]. While this may be open to debate, we only considered as evidence those studies with low risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…26 A similar report concluded that this therapy can reduce the intensity and frequency of pain in these patients. 17 In other studies among patients with fibromyalgia and lateral epicondylitis, pain levels decreased significantly after the application of craniosacral therapy. 8,9,12 However, these changes could be partially linked to a placebo effect, as reported by Xu et al 40 in LBP patients treated with acupuncture.…”
Section: Discussionmentioning
confidence: 97%
“…16 A preliminary report on the utility of craniosacral and triggerpoint therapy in LBP claimed that further research with randomized samples is required to determine the mechanism by which craniosacral therapy may effectively reduce the intensity and frequency of pain in LBP. 17 The purpose of the current randomized clinical trial was to analyze the effectiveness of craniosacral therapy on disability, pain intensity, kinesiophobia, isometric endurance of trunk flexor muscles, mobility, oxygen saturation, blood pressure, cardiac index, and biochemical estimation of interstitial fluid in individuals with chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Only four studies had the objective of analyzing the sEMG results among different MT treatment approaches. The effectiveness of craniosacral therapy techniques and trigger point therapy was examined and found that both can effectively reduce the intensity and frequency of LBP although craniosacral therapy (CST), unlike trigger-point therapy (TPT), reduces the tension at the multifidus muscles (Bialoszewski et al, 2014). The work of Ritvanen et al (2007) aimed to compare traditional bone setting (TBS) and physical therapy (PTh), also for LBP, indicating that both reduce the subjective feeling of pain, but TBS showed better results than PTh.…”
Section: Comparing Mt Treatment Protocolsmentioning
confidence: 99%